Pengaruh Ekstrak Daun Sirsak Terhadap Gambaran Histopatologi Pankreas Rattus Norvegicus Jantan yang Diinduksi Aloksan - RIFKY YOGA PRATAMA; NITA PRANITASARI; DIAH PURWANINGSARI (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Background: Diabetes melitus is a metabolic disorder characterized by an increase in blood glucose levels caused by disruption of the pancreas in producing insulin. Alloxan is a substrate that can trigger the condition of hyperglycemia which can cause diabetes because of its toxic nature to pancreatic beta cells. The aim of this study to find out about the effect of soursop leaf (Annona muricata Linn) extract in repaired to pancreatic tissue damage of male wistar rats (Rattus norvegicus) induced by alloxan. Method : 24 male Wistar rats, divided into 3 groups : K(-) group that no treatment, K(+) group that induced by alloxan dose 150mg/kgBW and K(p) group that induced by alloxan dose 150mg/kgBW and given soursop leaf extract dose 150mg/kgBW. Result : there was significant difference (p = 0.001) of pancreatic tissue damage measured by histopathologic score between group of no treatment rats compared to the group of rats induced by alloxan. There was a significant difference of pancreatic tissue damage measured by histopatology score group of rats induced by alloxan compared to group of rats induced by alloxan and given soursop leaf extract. Conclusion : the administration of alloxan significantly increases the pancreatic tissue damage and the administration of soursop leaf extract can improve pancreatic tissue damage measured by histopathology score because soursop leaf extract contains flavonoids and tannins which function as antioxidants.